A Quantitative Study of Intervertebral Disc Morphologic Changes Following Plasma‐Mediated Percutaneous Discectomy. Issue 10 (4th September 2014) - Smuck, Matthew; Levin, Joshua; Zemper, Eric; Ali, Adil; Kennedy, David J.
Abstract Objective To quantitatively evaluate interval magnetic resonance imaging (MRI) changes in disc morphology following plasma‐mediated percutaneous discectomy. Design/Setting A retrospective comparison of pretreatment and posttreatment MRIs at a single university spine clinic. Subjects From a group of 60 consecutively treated patients, 15 met the study inclusion and exclusion criteria. All had either failed treatment or had other clinical reasons for a posttreatment MRI. Methods Two independent physicians electronically measured disc protrusion size and disc height at the treatment discs and adjacent discs on pre‐ and posttreatment MRI scans. Additionally, images were compared for gross anatomic changes including disc degeneration by Pfirrman classification, new disc herniations, high intensity zone (HIZ), vertebral endplate changes, post‐contrast enhancement, and changes in segmental alignment. Pearson r correlation was used to determine interobserver reliability between the two physicians' MRI measurements. Paired t‐tests were calculated for comparisons of pre‐ and posttreatment MRI measurements, and an ANOVA was performed for comparison of pre‐ to posttreatment changes in disc height measurements at treatment levels relative to adjacent levels. Results Correlation was high for measurement of disc height change (r = 0.89; P < 0.0001) and good for anteroposterior protrusion size change (r = 0.51; P = 0.0512). Disc height at treated discs demonstrated a small but statistically significant mean interval reduction of 0.48 mm (P = 0.0018). This remained significant when compared with the adjacent control discs (P < 0.0001). Pretreatment mean disc protrusion size (4.74 mm; range 3.75–6.55 mm) did not differ significantly (P = 0.1145) from posttreatment protrusion size (4.42 mm; range 2.55–7.95 mm). Gross anatomic changes at treatment levels included reduced disc protrusion size (N = 6), enlarged protrusion (N = 3), resolution of HIZ (N = 3), and improvement in endplate signal changes (N = 1). Also, 11/15 posttreatment MRIs included post‐contrast images that showed epidural fibrosis (N = 1), rim enhancement (N = 2), and enhancement of the posterior annulus (N = 4). Conclusions Based on MRI examinations, subtle anatomic changes may occur following plasma‐mediated percutaneous discectomy. Further study is required to determine the clinical relevance of these changes.